FIGURATIVE LANGUAGE IN NOVEL OF LITTLE WOMEN BY LOUISA MAY ALCOTT (2022) - Salma Azzahra Khairunnisa; Juanda Juanda (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This research focuses on the Figurative Language in a novel Little Women by Louisa May Alcott. The purpose of this study is to find the types of figurative language, describe the meaning, and the dominant types of figurative language in the novel Little Women by Louisa May Alcott. This research focuses on the figurative language found in the novel, explaining the words or sentences in the novel which is a type of figurative language. The research method that will be used is a qualitative descriptive method by identifying, classifying, describing, and explaining the meaning of each figure of speech. From the results that the researchers found, the dominant figurative language in the novel is Simile. Keywords: Figurative language, Novel, Semantics